IMPLEMENTASI RENCANA AKSI NASIONAL HAK ASASI MANUSIA (RANHAM) PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN SIDOARJO - Wijaya, Davaniar Yoga; Prathama, Ananta (Jurnal Progress Administrasi Publik, 2024)
The National Human Rights Action Plan, hereinafter abbreviated as RANHAM, is one of the important commitments that Indonesia has within the human rights policy framework. This RANHAM policy is implemented by all Regencies/Cities in Indonesia based on Presidential Regulation No. 53 of 2021. One of the districts/cities that also implements this policy is Sidoarjo Regency. Problems regarding human rights will always occur in every region, one of which is Sidoarjo Regency, which is still full of a number of problems regarding human rights. The aim of this research is to find out the extent to which Sidoarjo Regency has implemented the RANHAM policy in 2023. The research was prepared using qualitative descriptive research methods with secondary data taken through interviews, literature reviews, and observation analysis. Apart from that, various sources were also explored to describe practices related to RANHAM, both from official government documents and various reports in print and electronic mass media. In this research it can be concluded that the 2023 RANHAM in Sidoarjo Regency has been implemented by carrying out 7 massive actions in collaboration with regional officials in Sidoarjo Regency. In the implementation of the 7 RANHAM actions, monitoring and evaluation were also carried out and several challenges were found in the implementation of each RANHAM action in Sidoarjo Regency, so it can be concluded that the implementation of RANHAM in 2023 in Sidoarjo Regency is still not optimal.   Keywords: Human Rights; Implementation; RANHAM